Survival COVID-19 in Adult Patients with Liver Cirrhosis - Gita Aprilicia; Syahrizal Syarif; Kemal Fariz Kalista; Andri Sanityoso Sulaiman; Irsan Hasan; Cosmas Rinaldi A Lesmana; Juferdy Kurniawan; Chyntia Olivia Maurine Jasirwan; Saut Horas Hatoguan Nababan; Rino Alvani Gani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: COVID-19 is a disease caused by infection of SARS-CoV-2 virus which leads to mortality due to respiratory failure. The progression of COVID-19 is more severe in patients with pre-existence morbidities, including liver disease. Recently, a few studie showed that liver cirrhosis patients with COVID-19 had a higher risk of mortality rather than liver cirrhosis patients without COVID-19 infection. Nevertheless, the study of survival COVID-19 in a patient with underlying liver cirrhosis is still limited. The aim of this study is to evaluate the survival of COVID-19 in adult patients with liver cirrhosisMethod: An observational study in Cipto Mangunkusumo Hospital was conducted. Patients with underlying liver cirrhosis between March 2020-January 2021 with positive confirmation of COVID-19 were enrolled in this study. Liver cirrhosis patients without COVID-19 were enrolled as a comparison. Both liver cirrhosis patients with and without COVID-19 were follow up at the time of hospital admission until 30 days outcome. Kaplan Meier and a log-rank test were conducted to evaluate the comparison of survival rate in liver cirrhosis patients with and without COVID-19. Multivariate Cox Proportional Hazard was conducted to identify the independent risk factors related to survival.Results: There were 22 liver cirrhosis patients with COVID-19 and 116 liver cirrhosis patients included in this study. Presentation of gender and age similar both of them. Predominantly males with average age were 57 years ± 13,60 for cirrhosis with COVID-19 patients and 53 years ± 12,75 for without COVID-19. The survival rate of liver cirrhosis patients with COVID-19 lower than liver cirrhosis patients without COVID-19  (35.8% vs. 67.2%, p-value 0.001). Median survival of liver cirrhosis patients with COVID-19 was 4 days (95% CI: 1-8 days), while median survival of liver cirrhosis patients without COVID-19 couldn’t be reached since the survival rate of this group above 50%. Final model Cox PH showed that liver cirrhosis with COVID-19 (HR: 8.99; CI 95%: 4.55 – 17.80, p-value 0.001) and Child-Pugh class C (HR: 5.61; 95% CI: 2.76 – 11.40, p-value 0.001) were the independent risk factors associated with poor survival.Conclusion: The survival rate of liver cirrhosis patients with COVID-19 lower than liver cirrhosis patients without COVID-19. Liver cirrhosis with COVID-19 and Child-Pugh class C were associated with poor survival.